TAMAN BERMAIN DENGAN PENDEKATAN ARSITEKTUR HIJAU DI SUKOHARJO - Tri Hesti Shinta Dewi; Maya Andria Nirawati; Kusumaningdyah Nurul Handayani (Universitas Sebelas Maret Surakarta, 2015)
The background of Playground design in Sukoharjo is the lack of container for recreational play area and the lack of green spaces in Sukoharjo. As an example of the present is the of variety games for children in Sukoharjo square, which makethe location become dense and crowded so it can cause the possibility of an accident. The Games also don’t have education value in it, whereas public space as a place of recreation that educate is necessary to increase the interest in learning, especially for children. Listed on thr Spatial Plan Sukoharjo period 2010-2030, Sukoharjo have a plan that there is a place for recreation development. Problem design is how for designing educative and recreative playground place or recreation that fit for all ages. The method is based on the concept of Green Architecture with the cozy atmosphere is created by the climate-responsive design and environmentally friendly. The obtained result is a playground that makes the architectural elements of design principles are explored, that building is climate-responsivie design and enviromentally friendly. Green archintecture is also applied as a means of education and recreation,the use of recycled goods for furnituture site and building materialswhich also privide insight and education for society that the goods are considered to be unusable apparently still can be used again. Keywords: Educative, Green Architecture, Playground, Public Space, Recreation